Marine Spatial Planning-Based Siting Methodology for Co-Located Offshore Wind and Wave Energy - Cullen, Emily; Fitzgerald, Breiffni (My University, 2026)
This paper develops a marine spatial planning (MSP) methodology for strategic siting of co-located offshore wind and wave energy systems, demonstrated for Ireland’s west coast. Although Ireland has exceptional wind and wave resources, objective spatial methods for assessing combined development potential remain limited. The proposed framework integrates a two-stage screening process comprising Boolean exclusion criteria and a weighted multi-criteria suitability index (SI) spanning technical, environmental, and socio-economic factors. The western Irish Exclusive Economic Zone is discretised into 189 grid cells, and site conditions are quantified using 20 years of ECMWF ERA5 metocean data (2002–2022) together with marine-use, environmental protection, and infrastructure datasets from Ireland’s Marine Atlas and associated public sources. Three representative west-coast locations were evaluated in detail. Under the equal-weighting scenario, the site at 52.5° N, 10° W (approximately 40 km west of Moneypoint) achieved the lowest SI score (4.231) and was therefore ranked most suitable compared with 6.634 at 52° N, 11.5° W and 8.093 at 54° N, 10.5° W. The selected site combines comparatively low spatial constraints with favourable depth (−52.4 m) and moderate wind–wave correlation (r = 0.4636), while the resource assessment confirms strong west-coast conditions overall. The framework provides a transparent, transferable, and stakeholder-informed decision-support methodology for early-stage MSP and strategic siting of hybrid offshore renewable energy developments in Ireland and other maritime regions.
PUBLISHED
Keywords: offshore wind; wave energy; marine spatial planning; environmental planning; marine protected areas; Smart & Sustainable Planet; Environmental planning and sustainable development; Wind Energy and Wind Turbines; wave energy